Denial of Rights, Denial of Justice: The Embera Katío - Rebolledo Vargas, Jairo Alfonso (DIXI, 2018)
Aim: This article explains the situation of displacement to which the Embera Katío people were forcedas a result of the construction of the Urrái hydroelectric power plant (Alto Sinú-Córdoba), deprivingthis minority group of its territorial and cultural heritage and causing its imminent disappearance as acommunity. Methods: The document shows how political and judicial corruption—through its questioned deci-sions—caused the Embera Katío community to be “expelled” from their ancestral territories and relo-cated in the urban area of the municipality, where they could not carry out their agricultural, educatio-nal, religious, fishing and navigation, etc. activities. Therefore, its members were subjected to a processof adaptability to a new life system until “disappearing” as an ethnic group. Results: Despite the existence of national and international legislation that protects the rights of indi-genous communities and minorities, there was no effective application of the law in this case so that,when the Constitutional Court intervened, it faced accomplished facts. Conclusion: The judicial authorities’ failure to timely obey the orders of the National Constitution andinternational treaties led to a situation of eviction, displacement and subsequent disappearance byacculturation of the Embera Katío community from Alto Sinú.
Keywords: fundamental indigenous rights; prior consultation; political corruption; Embera Katío natives; denial of justice; Urrá i dam